Perilaku Berwirausaha Generasi Milenial di Era Pandemi COVID-19 - Hasan, Muhammad; Arisah, Nur; Sasmita, Fira Ayu; Miranda, Miranda; Putri, Aisyah Amaliyah; Pattisina, Chatrien Dione (Universitas Pendidikan Ganesha, 2021)
This study aims to study and reveal the entrepreneurial behavior of the millennial generation during the COVID-19 pandemic. This study is a study with a quantitative approach with survey techniques. Data collection was carried out using an instrument in the form of a questionnaire and completed with interviews with millennials who have businesses, in order to obtain a comprehensive picture of entrepreneurial behavior. There are four aspects measured in this study, namely entrepreneurial interest, creativity, innovation, and product marketing strategies carried out by millennials during the COVID-19 pandemic. The population in this study were millennials who have businesses and are domiciled in South Sulawesi Province, West Sulawesi Province and Southeast Sulawesi Province with purposive sampling of 31 people. The results of this study show that during the COVID-19 pandemic, the millennial generation still has an interest and enthusiasm for entrepreneurship. This is shown by even though they are currently in the era of the COVID-19 pandemic, millennials still have entrepreneurial behavior, such as creativity, innovation, and marketing strategies to sustain their business during the COVID-19 pandemic.Â